Virus and host cell DNA syntheses during infection of Acholeplasma laidlawii by MVL3, a nonlytic cytocidal mycoplasmavirus. - Haberer, K (1980)
The replication of mycoplasmavirus MVL3 in Acholeplasma laidlawii K2 host cells was studied by analysis of infected-cell lysates using sedimentation in sucrose gradients and DNA-DNA hybridization. Viral DNA replication was found to involve intermediates sedimenting faster than free viral DNA, which is a linear, double-stranded molecule of about 26 x 10(6) daltons. After the shutdown of cellular DNA synthesis, viral DNA synthesis continued for many hours. The fate of cellular and parental viral DNAs was examined.